2014
DOI: 10.1101/gad.246272.114
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative 14-3-3 interaction screen connects the nuclear exosome targeting complex to the DNA damage response

Abstract: RNA metabolism is altered following DNA damage, but the underlying mechanisms are not well understood. Through a 14-3-3 interaction screen for DNA damageinduced protein interactions in human cells, we identified protein complexes connected to RNA biology. These include the nuclear exosome targeting (NEXT) complex that regulates turnover of noncoding RNAs termed promoter upstream transcripts (PROMPTs). We show that the NEXT subunit RBM7 is phosphorylated upon DNA damage by the MAPKAPK2 kinase and establish that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
68
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(72 citation statements)
references
References 34 publications
(44 reference statements)
4
68
0
Order By: Relevance
“…Indeed, in a very recent publication, the phosphorylation of RBM7 by MK2 upon UV-C light exposure on S136 and S204 was demonstrated and constitutes a 14-3-3 protein binding site preventing rapid PROMPTs degradation by the nuclear RNA exosome (Blasius et al 2014). These findings clearly complement the mechanism elaborated in this manuscript and could explain the remaining phosphorylation signal seen for Rbm7 S136A in the radioactive kinase assay (Supplemental Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, in a very recent publication, the phosphorylation of RBM7 by MK2 upon UV-C light exposure on S136 and S204 was demonstrated and constitutes a 14-3-3 protein binding site preventing rapid PROMPTs degradation by the nuclear RNA exosome (Blasius et al 2014). These findings clearly complement the mechanism elaborated in this manuscript and could explain the remaining phosphorylation signal seen for Rbm7 S136A in the radioactive kinase assay (Supplemental Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In the same study, RBM7 and RBM7 S136A,S204A were used to specifically precipitate PROMPTs. It was shown that RBM7 loses its PROMPTsbinding capacity during UV-stress and that this loss is completely abrogated using the RBM7 S136A,S204A double mutant (Blasius et al 2014). These observations are in line with our CLIP-results although the effects for the Rbm7 S136A single mutant and the p38 MAPK -inhibitor BIRB796 ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In this yeast, the phosphorylation of Cdc25 by Srk1 causes Cdc25 binding to Rad24 (17), and in mammalian cells, protein phosphorylation by the functionally homologous kinase MK2 promotes interaction with different 14-3-3 proteins, some connected to the DNA damage response (66). In A. nidulans, the Cdc25 ortholog NimT also controls DNA damage checkpoint, regulating NimX (Cdc2 ortholog) activity (67).…”
Section: Figmentioning
confidence: 99%
“…Indeed, it was recently suggested that the DNA damage response (DDR) entails the phosphorylation of the RBM7 protein, which is an integral component of the nuclear exosome targeting (NEXT) complex connecting at least a subset of PROMPTs to decay by the exosome. [14][15][16][17] Such phosphorylation of RBM7 appears to alter the affinity of the protein for RNA, resulting in the accumulation of selected PROMPTs during the DDR due to their inefficient targeting by the NEXT complex.…”
Section: Introductionmentioning
confidence: 99%